Akulturasi Psikologis para Self-Initiated Expatriate - Sari, Ginda Rahmita; Subandi, - (Gadjah Mada Journal of Psychology, 2015)
Expatriation has become a phenomenon that can be found in many parts of the world as entering globalization era. Expatriation has been done not only by employees that were assigned by their company but also by individuals who choose to develop their capabilities by having cross cultures experiences and become a self-initiated expatriate. The aim of this study was to find meaning and process of self-initiated expatriate psychological acculturation in Yogyakarta. This study used phenomenological qualitative approach to comprehend meaning of self-initiated expatriate psychological acculturation in Yogyakarta. Data was gathered through in-depth interviews with six self-initiated expatriates that has built a new life in Yogyakarta with their spouse. The research findings showed that respondents chose to be self-initiated expatriates in Yogyakarta to seize an opportunity of a better living in Yogyakarta. In acculturation process, they develop two kinds of coping, adopting new culture and maintaining original culture. They combined both cultures values in their selves that caused changes in their cognitive, behavior and attitude and became an integrated self as a result. Further findings showed that coping variation was selected by considering their condition, situation, needs and interests.Keywords: self-initiated expatriate, culture, psychological acculturation